ANALISIS KONSEP GREEN ECONOMY TERHADAP POTENSI PENGEMBANGAN PARIWISATA HALAL DI SUMATERA UTARA - Tiara Ermelia; Imsar Imsar; Rahmat Daim Harahap (Jurnal Proaksi, 2023)
Halal tourism plays an important role in achieving sustainable development. Sustainable development which is a global issue that affects every aspect of human life namely economic, social and environmental is also included in the halal concept. . descriptive steps researchers used to describe the data obtained using qualitative research methods. The information gathering strategy is completed by meeting and perception. The results of this study are that the utilization of the Green Economy in the potential for creating a halal travel industry in North Sumatra cannot be carried out considering that there are not many supporters for the halal travel industry, for example places of worship, halal food, sharia lodging, the benefits of local companions whose halal status is not guaranteed. Even though North Sumatra has been right to implement halal tourism in terms of tourist objects because North Sumatra's tourist attraction, Lake Toba, is one of the priority tourist destinations that have supported a green economy.